Answer: 30 Pins
Step-by-step explanation:
I solved it on khan academy
Answer:
Step-by-step explanation:
The question isn't clear...
Answer:
store A- 4
Store B-1
Store C-3
Store D- 2
Step-by-step explanation:
gotta help a brotha out if i was correct Drop a sub at iToxicMakersYT
Six million three hundred sixty two thousand forty nine
Answer:
(2)
Step-by-step explanation:
Let f(x) = y → f-¹(x) = f(y) = x, f(y) is the inverse of f(x)
Thus,
=> -x³ - 9 = y
=> - y - 9 = x³
=> (-y - 9)^(1/3) = x
=> f(y) = x
Inverse is (-y-9)^(1/3)
Replacing the variable, inverse is (-x-9)^(1/3)
Option (2)